Pelegongan Music Composition “Kasmaran | Komposisi Gamelan Pelegongan “Kasmaran” - Anom Widara; I Ketut Muryana (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
This work has a percussion form created by petegak pelegongan, entitled “Kasmaran”. This work is transformed from a phenomenon of love that the stylist feels or from the stylist's own personal experience into a musical work of art with the media saying Gong Kebyar and two ungguh gender vines and does not use the reong instrument found in the barungan Gong Kebyar, because it is seen from the context of the gamelan Pelegongan. do not use a reong instrument. The form of this claim cannot be separated from the elements of existing traditions, this work consists of three parts, namely kawitan, pengawak and pengcet. The arrangement of musical elements in terms of song structure, playing techniques and gending motifs was redeveloped by processing musical elements such as tone, melody, tempo, rhythm and dynamics. In addition to these things, general aesthetic characteristics such as unity (wholeness, compactness, cleanliness), complexity (complexity) and intensity (strength, sincerity, belief) are also used as references in realizing artistic works to give artistic weight to Kasmaran's musical works of high quality.